ABDULLATĠF HARPUTÎ VE ĠSLAM DÜġÜNCESĠNDE YENĠLĠK ARAYIġLARI - SÖNMEZ, Vecihi (Scientific Journal of Faculty of Theology, 2015)
Islamicthought is seekingfor a newsuddenadvance in today‘scentury. It is essential that, Muslims and their Islamic perceptiveness interrogate their selves about the facts of the new century. Especially in the last decades, losing blood of Islamic world against west has been understood as a weakness of Islam religion, at the same time many important problems appeared because Muslims could not solve the most significant issues of the century and had problems to object to the pressure of new thought systems. Members of this thought who support a sophisticated civilization in the certain periods of the history are lately in decline. On the contrary, Harputi who seems faithful for the traditions of the Kalam had considered the knowledge of the previous Kalam scholars but he had also been open to changes and improvements of the new century. İlahiyat Fakültesinin Ilmi Dergisi – 20-21. Sayı 2015 136 More importantly, Harputi had been worried about that; some ongoing political and religious sects in Islamic world and the new philosophers in the west have a bad influence on the principles of faith of Islam. So it was needed to answer and solve the new problems. In that regard, the positivist and naturalist opinions against religion are never accepted and correct. Harputi asserts his own opinions from these opinions and tries to convince us about the legitimacy of divine knowledge based on monotheism. My aim in this article is to investigate his scientific personality and what new he added to Kalam.